Stable alteration of pre-mRNA splicing patterns by modified U7 small nuclear RNAs - Gorman, Linda (The National Academy of Sciences, 1998)
In several forms of β-thalassemia, mutations in the second intron of the β-globin gene create aberrant 5′ splice sites and activate a common cryptic 3′ splice site upstream. As a result, the thalassemic β-globin pre-mRNAs are spliced almost exclusively via the aberrant splice sites leading to a deficiency of correctly spliced β-globin mRNA and, consequently, β-globin. We have designed a series of vectors that express modified U7 snRNAs containing sequences antisense to either the aberrant 5′ or 3′ splice sites in the IVS2–705 thalassemic pre-mRNA. Transient expression of modified U7 snRNAs in a HeLa cell line stably expressing the IVS2–705 β-globin gene restored up to 65% of correct splicing in a sequence-specific and dose-dependent manner. Cell lines that stably coexpressed IVS2–705 pre-mRNA and appropriately modified U7 snRNA exhibited up to 55% of permanent restoration of correct splicing and expression of full-length β-globin protein. This novel approach provides a potential alternative to gene replacement therapies.